Research on load capacity of concrete filled columns with battened steel sections - Szmigiera, Elzbieta; Zoltowski, Wojciech; Siennicki, Miroslaw (Journal of Civil Engineering and Management, 2010)
The paper presents experimental and numerical results for selected built‐up steel columns filled with concrete. The laboratory tests were accompanied by numerical analysis carried out using general purpose, finite element program ABAQUS. Based on heretofore research presented in this paper, one may assumes that the application of concrete filled columns with battened steel sections is economically very profitable. For columns filled with concrete strength class C20/25 the increase of load bearing capacity was 42% and for elements filled with concrete strength class C50/60 ‐ above 100%. The application of the shorter distance between battens allowed to obtain additional increase of ultimate load (for concrete C20/25 ‐ about 8%). The numerical analysis also confirmed the increase of the load capacity for the columns. The best correlation between numerical and experimental results was obtained for the assumed eccentricity of 1 mm. Moreover the higher rigidity of those members in relation to steel columns is not connected with significant increase of the cost. The study was conducted as a part of the research project nr 4TO7E01528, founded by the Polish Ministry of Science and Higher Education. First Published Online: 10 Feb 2011